Mapping the Literature Trends of Internal Auditing in the United States: A Systematic Review and Directions for Future Research - Saddam A. Hazaea; Chun Cai; Ebrahim Mohammed Al-Matari; Mohammed A. Al-Bukhrani; H. Gin Chong (SAGE Open)
This review study examines the existing literature on internal audit (IA) in the United States to identify how internal audit functions (IAFs) have evolved in response to global shifts in business practices. Despite growing attention to IA, the literature remains fragmented, limiting a comprehensive understanding of how IA has evolved in response to business practices. Through a systematic review, this study analyzes 171 studies published between 1984 and 2023 retrieved from the Scopus database. This study investigates the characteristics of the literature and topics discussed, focusing on six key aspects: the practice of IA, the role of IA, the quality of IA, information technology (IT) auditing, risk management, and the relationship between IA and other parties. The results reveal a paradigm shift in the activities undertaken by internal auditors and a significant transition in the literature from discussing traditional topics to new topics related to environmental changes, the climate crisis, geopolitical challenges, and technological developments. The results also emphasize the need for more theory-based, empirical, and comparative studies on IA in different contexts and sectors. This paper identifies substantial gaps in IA literature and proposes directions for future research agendas, particularly concerning the influence of politics, culture, and the effects of COVID-19 on IA practices. These insights provide valuable guidance for IA practitioners, researchers, standard setters, and the Institute of Internal Auditors (IIA) in refining frameworks and understanding global IA trends.